Adaptation and pilot implementation of a hereditary cancer risk-assessment tool for primary care - Sukh Makhnoon; Anoop Gurram; Eyad Alrabbat; Tiwatope Ibidapo; Ying Ma; Emanuel Villa; Michael E. Bowen; Sayoni Lahiri; Celette Sugg Skinner; Sara Pirzadeh-Miller; Steven Leach (BMC Primary Care)
Abstract Background Family history-based risk assessment for hereditary breast and ovarian cancer is guideline-recommended but clinical implementation remains limited. This is likely, in part, because it adds to the limited time primary care providers (PCPs) have to implement all guideline-recommended care. Methods We adapted Family History Screening 7 (or FHS7), designed for administration by a PCP, for self-report by primary care patients. We used the Framework for Reporting Adaptation and Modifications to Evidence-based Implementation Strategies (FRAME) to guide the modifications. We conducted a pilot feasibility study of hereditary prevention program using the adapted risk-assessment tool and report results from the first year of the program (February 2023-March 2024). Results Feedback from clinical stakeholders and our literature review revealed that, while hereditary cancer risk assessment was a priority for the primary care setting, implementation by PCPs was not feasible. We therefore adapted FHS7 for patient self-report by separating double-barreled items and eliminating jargon, resulting in nine items– six with binary (yes/no) and three with numeric responses. Outcomes from pilot implementation of the adapted FHS7 (n=4,355) showed high completion rate (77% completed all items), with greater completion via MyChart than in-person (87% vs. 13%), and higher non-response for the three items with numeric responses compared to the six with binary responses. Overall, positivity rate of the adapted FHS7 was 36%. Conclusion This paper describes our team’s process of adapting the FHS7 questionnaire to retain the core function (evaluating specific family history of cancer information) while adapting to fit the clinical context. Preliminary implementation data suggest high completion rate in the primary care setting.